NEW FACTORS THAT AFFECT THE ACTIVITIES OF THE REQUIREMENTS ELICITATION PROCESS - L. R. WONG (Journal of Engineering Science and Technology, 2018)
Given that requirements elicitation is one of the important stages in software development, many researchers agree that incorrect, incomplete and confusing requirements have a great negative impact on the quality, cost and delivery time of software projects. Therefore, factors that affect requirements elicitation and the activities of its process have been identified. However, there are no studies on what factors affect the activities Integration, Documentation and Refinement. Moreover, the theories of organizational behaviour, organizational learning, Technology acceptance model, among others, provide factors not studied in the area of requirements elicitation. The purpose of this research is to identify new factors that influence each activity of the requirements elicitation process and, consequently, the quality. Hence, in the present paper seven new factors that affect the activities of the requirements elicitation process are presented: learning capacity, negotiation capacity, permanent staff, perceived utility, confidence, stress, and semi-autonomous. In addition, 17 relationships (factor-activity) have been introduced. An empirical study was carried out on 182 respondents, obtaining, from the analysis of simple and multiple correspondences, that all the proposed factors have an influence between "High" and "Very high". Furthermore, the hypothesis test T-Students, with 95% confidence, verifies that 15 of the 17 relationships are valid.